PEMBELAJARAN YOGA ASANAS PADA SISWA SD PGRI KOTA DENPASAR - Kadek Oka Prima Arta; Marsono; I Wayan Lali Yogantara (UHN IGB Sugriwa Denpasar, 2020)
Formal education is one of the keys to the development and improvement of children's self- quality and behavior, especially elementary school education. This is where the role of educators is to provide education to students in accordance with the functions and objectives of National education which is carried out through various activities, one of which is through learning yoga asanas. Development in the field of education is very important in producing quality human resources. One of the institutions that have aspirations to make this happen is SD PGRI Denpasar City. The problems discussed include: (1) How is the process of implementing yoga asanas for elementary school students at PGRI Denpasar City? (2) What educational values are contained in learning yoga asanas for SD PGRI students in Dnepasar City? (3) What is the role of learning yoga asanas in SD PGRI Denpasar City students?. The theories used to analyze the problem are humanistic learning theory, value theory and role theory. The data collection methods used are observation, interviews, literature studies, and document studies. The data that has been collected is analyzed using a qualitative descriptive analysis method with steps of data reduction, data presentation and drawing conclusions. The technique of presenting the results of data analysis is presented formally and informally. The results of the study show: (1) The process of implementing yoga asanas for elementary school students at PGRI Denpasar City includes the stages of preparation, introduction, prayer, stretching, calming, Suryanamaskara and asanas, meditation and closing prayers, (2) Educational values contained in learning yoga asanas for students of SD PGRI Denpasar City, namely the value of religious education, the value of ethical education, the value of discipline education, the value of multicultural education and the value of health education, (3) The role of learning yoga asanas in SD PGRI Denpasar City students is to increase students' sraddha and devotional service, increase orderliness of students, increasing student tolerance, maintaining physical and spiritual health of students and developing student skills.